Placental damages from ultrasonic changes to histopathological findings in maturing placenta in pregnancy complicated with hypertension: an observational clinical study - Dutta, Amit; Sahu, Ramesh Kumar; Chatterjee, Kripasindhu; Kothari, Sanjay; Rahaman, S. K. Rafikul; Sen, Shipra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The development of mild hypertension or preeclampsia at or near term is associated with minimal maternal and neonatal morbidities. Obstetric ultrasound provides a cornerstone to other modalities used for assessing hypertensive disorders of pregnancy. Placental architecture is modified in PE and eclampsia. This study was designed to detect the placental changes in hypertensive disorders of pregnancy and correlation with ultrasonic and histopathological changes. Methods: The study group comprised of 42 patients with pregnancy complicated with hypertension with period of gestation above 20 weeks and B.P. more than 140/90 mm of Hg measured on two occasions 6 hours or more apart. The control group consists of 42 normotensive patients matched with age and parity. One ultrasonic examination was performed between 28 weeks and 34 weeks and another after 34 weeks till term. Apart from routine parameters i.e. BPD, AC, FL, Amniotic fluid index, EBW and gestational age routine placental grading were performed according to the classification proposed by Grannum and associates. To evaluate perinatal outcome following measurement were studied birth weight immediately after delivery, mode of delivery, perinatal morbidity and mortality, APGAR score, presence of fetal distress. Results: In 97.62% cases (41 out of 42) of control group showed Grade–II changes as opposed to 57.14% of cases (24 out of 42) in study group before 34 weeks. All 21 cases in study group showing Grade ‘III’ changes before 34 weeks had infarction, calcification, increased syncytial knots, fibrinoid necrosis from 95.23 to 100% of these cases showed all these changes. Only 2 cases (9.52%) showed perivascular hemorrhage having Grade ‘III’ before 34 weeks. Conclusions: Accelerated maturation of placenta in pregnancy complicated with hypertension are more common in the hypertensive group. Increased histopathological degenerative changes e.g. calcification, fibrinoid necrosis etc., are more marked even before 34 weeks of gestation in hypertensive group.